(untitled) (The Research of Medical Science Review, 2025)
Background: Neoadjuvant chemotherapy (NAC) is widely employed in the management of breast cancer to reduce tumor burden, improve surgical outcomes, and allow for breast-conserving procedures. However, the optimal interval between the completion of NAC and definitive surgery—referred to as time to surgery (TTS)—remains a subject of ongoing debate. Concerns primarily revolve around whether early or delayed surgery post-NAC influences the rates of postoperative wound complications and operative mortality. Objective: To evaluate the impact of timing of surgery after NAC on postoperative wound infections and operative mortality in patients undergoing surgery for breast cancer. Methods: This randomized controlled trial was conducted at the Department of General Surgery, Nishtar Medical University/Hospital, Multan, over a period of six months from May 2024 to October 2024. A total of 60 female patients aged 30–65 years, diagnosed with grade I or II breast cancer and having completed a standardized NAC regimen, were enrolled. Patients were randomly allocated into two groups: Group A (Early Surgery): Underwent definitive surgery within 3 to 6 weeks of completing NAC. Group B (Delayed Surgery): Underwent surgery more than 6 weeks after completing NAC. Postoperative outcomes, including wound infections and operative mortality, were assessed and recorded during a 30-day postoperative follow-up period. The occurrence of wound infection was diagnosed clinically based on signs of erythema, warmth, purulent discharge, and delayed wound healing. Operative mortality was defined as death occurring within 30 days of surgery. Comparative analysis between the groups was performed using the chi-square test, with a p-value ≤ 0.05 considered statistically significant. Results: A total of 60 patients were enrolled, with 30 in the Early Surgery group and 30 in the Delayed Surgery group. There were no significant differences in baseline characteristics such as age, BMI, and blood loss between the groups. Postoperative outcomes showed similar wound infection rates (30.0% vs. 20.0%, p=0.37). However, operative mortality was significantly higher in the Delayed Surgery group (16.7%) compared to the Early Surgery group (0%), with a p-value of 0.02, suggesting that early surgery may reduce the risk of mortality. Conclusion: Early surgery within 3–6 weeks after neoadjuvant chemotherapy (NAC) in breast cancer patients significantly reduces operative mortality compared to delayed surgery. Timely tumor resection before disease progression improves survival outcomes, despite no significant difference in wound infection rates. This supports the benefit of early surgery for better overall patient outcomes.